Grinding force modelling for ductile-brittle transition in laser macro-micro-structured grinding of zirconia ceramics. Issue 15 (15th October 2019) - Zhang, Xiaohong; Kang, Zhongxiong; Li, Si; Shi, Zhaoyao; Wen, Dongdong; Jiang, Jie; Zhang, Zhicheng
Abstract: Laser ablation accomplishes high geometrical adaptability by the use of pulsing lasers and permits the manufacture of macro-micro-structures. In this paper, a systematic approach with a laser structuring technology was devised and utilized to generate macro-micro-structured patterns on the diamond wheel surface. An experiment on zirconia ceramic grinding was performed by the macro-micro-structured wheel. The grinding force and the surface morphology were investigated. The forming mechanism of the three grinding stages was analyzed, including ductile-stage grinding, ductile-to-brittle-transition-stage grinding and brittle-stage grinding. A theoretical grinding force model was presented by taking into account the three grinding stages in laser macro-micro-structured grinding (LMMSG). In addition, the mean grinding depths were defined in grinding force modelling for the ductile area, the ductile-to-brittle-transition area and the brittle area, separately. The amount of effective diamond grains was proposed for the final grinding force model. The model revealed the connection between the grinding force and the grinding parameters. Finally, the model was verified by experiments, and the experimental results were coincided with model predictions. It was obvious that the theoretical grinding force model may be available to predict the grinding force of zirconia ceramics under the LMMSG condition. Meanwhile, the influence between the grinding parameters and the surface morphology were discussed. The experimental results verify that the three grinding stages were existed and the theoretical model was proved to be reliable.